MOTIVASI SEBAGAI MEDIATOR DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DI SMA NEGERI 1 GRATI - Fiatri, Lilik (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
Administrative staff of SMA Negeri 1 Grati, Pasuruan Regency have an important role in developing the quality of school work, which can be achieved through high ability, motivation, and competence in carrying out their responsibilities. Although the performance of SMA Negeri 1 Grati employees, Pasuruan Regency is quite good, there are still problems with low work discipline and competence, as seen from non-compliance with work hours and disciplinary regulations. This study aims to determine the effect of work discipline and competence on employee performance with motivation as an intervening variable at SMA Negeri 1 Grati, Pasuruan Regency. The type of data used in this study is primary data with a questionnaire method distributed to 40 employees of SMA Negeri 1 Grati, Pasuruan Regency. Hypothesis testing was carried out using the bootstrap resampling method on SmartPLS 3.3. The results of the study showed that although work discipline and competence had a positive effect on employee performance, the effect was not statistically significant. Work discipline also had a positive but not significant impact on motivation. Meanwhile, competence was shown to have a significant positive effect on motivation. However, higher motivation actually had a negative effect on employee performance, although this effect was also not significant.